1990
DOI: 10.1002/neu.480210115
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic dynamics at the neuromuscular junction: Mechanisms and models

Abstract: During development, the neuromuscular junction passes through a stage of extensive polyinnervation followed by a period of wholesale synapse elimination. In this report we discuss mechanisms and interactions that could mediate many of the key aspects of these important developmental events. Our emphasis is on (1) establishing an overall conceptual framework within which the role of many distinct cellular interactions and molecular factors can be evaluated, and (2) generating computer simulations that systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…This question emerges out of a CNTF Regulates Synapse Elimination DevNeurosci 1996;18:185-198 long-held belief that synapse elimination is a competitive process, i.e., synapses compete for a trophic substance that is supplied by the target cells in limited amounts [recent reviews : Betz et al, 1990;Lichtman and BaliceGordon, 1990;Herrera and Werle. 1990;Van Essen et al, 1990;Colman and Lichtman, 1993]. The results of three different experiments described in this report indi cate that CNTF delivered during synapse elimination in the LA muscle results in 2 -3 times more multiple inner vation than normal.…”
Section: Discussionmentioning
confidence: 61%
“…This question emerges out of a CNTF Regulates Synapse Elimination DevNeurosci 1996;18:185-198 long-held belief that synapse elimination is a competitive process, i.e., synapses compete for a trophic substance that is supplied by the target cells in limited amounts [recent reviews : Betz et al, 1990;Lichtman and BaliceGordon, 1990;Herrera and Werle. 1990;Van Essen et al, 1990;Colman and Lichtman, 1993]. The results of three different experiments described in this report indi cate that CNTF delivered during synapse elimination in the LA muscle results in 2 -3 times more multiple inner vation than normal.…”
Section: Discussionmentioning
confidence: 61%
“…In our experiments, relatively high concentrations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) pM) of the calpain I inhibitor produced synapse reduction even in the absence of stimulation. (There was a modest, statistically nonsignificant tendency for leupeptin, cystatin, and aprotinin to do this also.)…”
Section: Discussionmentioning
confidence: 64%
“…These molecules may be involved in important processes such as neurite outgrowth (3), synaptic plasticity (4), and degeneration due to age or injury in the nervous system (5). The action of calcium-activated proteases has been put forward (6-8) as one of several hypotheses for the basis of activity-dependent synapse reduction at the neuromuscular junction (9).To further investigate the molecular mechanisms involved in activity-dependent synapse reduction, we developed an in vitro model by forming neuromuscular junctions in a threecompartment chamber culture system. Our previous results showed that in this culture system, cholinergic synaptic connections were reduced by about 50% after 24 hr of stimulation (10), indicating that the synapse reduction in this system is activity-dependent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the overall rate of decay might increase with a cell's average degree of activation, which in turn would increase with the total synaptic strength received by a cell. Increased activation could increase release of a molecule that degrades synapses, such as a protease, or decrease release of a molecule that supports synapses, such as a trophic, adhesion, or sprouting factor (evidence for such mechanisms is reviewed in Van Essen et al 1990). Increased activation might also increase decay due to thresholds for synaptic modification, as just discussed.…”
Section: Use Ofmentioning
confidence: 99%